Socioeconomic differentials in male mortality in Ireland: 1984-2008 - Richard Layte; Anne Nolan (The Economic and Social Research Institute (ESRI), 2013)
The presence of pronounced inequalities in mortality and life expectancy across income, education and social groups is now well established. Research across a large number of developed and wealthy countries, including Ireland, has shown that those with fewer resources, less education or a lower occupational class have higher standardised mortality rates (SMRs) than more advantaged individuals. Research for Ireland for the period 1989-1991 indicated that men in the unskilled manual social class had a mortality rate 2.8 times that of men in the higher professional social class. However, serious issues with the occupational coding of mortality data for the years since 1991 have meant that there has been no subsequent analysis of trends in socio-economic inequalities in mortality. The period since then has been characterised by an unprecedented boom and bust in economic activity which may well have influenced mortality differentials between socio-economic groups. The SMR in 2008 was 37% lower than in 1984 and 30% lower than in 1995. Using annual mortality data from the CSO over the period 1984-2008, this paper examines whether the overall downward trend in mortality observed over this period was experienced equally by all socio-economic groups (SEG) whilst adjusting the SMRs to take account of the coding issues effecting data on occupation/SEG. We use three methods to deal with the coding issues in the data across time: direct adjustment; imputation and a fully Bayesian imputation. Using these approaches we find that the differential in SMRs between professional and unskilled men aged 15+ decreased between 1984 and the early 1990s but then increased significantly thereafter as the SMR for professional men continued to decrease whilst that of unskilled men stabilised and then began to increase.
Keywords: 330